Analisis Aliran Udara Alat Penghemat Energi Vertikal Generasi Kedua untuk Masyarakat Tebing Gerinting Kecamatan Indralaya Selatan Kabupaten Ogan Ilir - darmawi darmawi; Qomarul Hadi; Ellyanie; Irwin Bizzy (Jurnal Rekayasa Mesin, 2021)
Alat Penghemat Energi Vertikal which is the patent rights of Sriwijaya University  with identity number of IDP 000065109 is already developed in order to raised up the efficiency and the effectivity as energy saver and as heat and exhaust gas eliminator to prevent the users for health and comfortable matters. This product is now called Alat Penghemat Energi Vertikal Generasi Kedua (APEV-2). Among the improvements are the legs of APEV-2 is now made of steel, the base flat is also made of steel. The front air  window area is decreased and the  rack window binder and air hole at the bottom of the APEV-2.